The Impact of Technological Advancements on HR Practices in Saudi Arabian Organizations - Alsalman , Asmahan Ibrahim (Journal of Ecohumanism, 2025)
This study investigates the impact of technological advancements on human resource (HR) practices within organizations in Saudi Arabia, aiming to understand how modern technologies are reshaping HR functions and strategies. Employing a mixed-methods approach, the research was conducted using two primary data collection techniques: an online survey and in-depth interviews. The online survey garnered responses from 200 HR professionals from various industries in Saudi Arabia, providing quantitative insights into the current trends, benefits, and challenges associated with the integration of technology in HR practices. Additionally, 50 semi-structured interviews were conducted with HR managers and executives to gain qualitative perspectives and deeper understanding of the strategic implications and experiences related to technology adoption in HR processes. The findings reveal significant transformations in recruitment, talent management, and employee engagement, driven by technologies such as AI and data analytics. However, the study also highlights challenges such as the need for skill development and change management to effectively leverage these technologies. This research offers valuable contributions to both academic literature and practical applications, suggesting strategies for organizations to optimize their HR practices in the era of digital transformation.